Overlap of IgG4-Related disease with autoimmune rheumatic diseases: Report of 2 cases and review of literature - Shivraj Padiyar; Abhilasha Manwatkar; Arvind Ganapati; Sanjeet Roy; John Mathew (Indian Journal of Rheumatology)
Immunoglobulin G4-related disease (IgG4-RD) is a systemic autoimmune disorder with a variety of manifestations. Association with other systemic autoimmune diseases is uncommonly reported in the literature. Hence, we intended to understand better the uniqueness of the overlapping associations of IgG4RD with other systemic autoimmune diseases. Retrospective electronic medical records-based review of IgG4RD occurring as an overlap with other systemic autoimmune diseases seen in the rheumatology department was done. We present two cases of IgG4 disease overlapping with systemic rheumatic diseases with a brief review of the literature. The first case was an overlap IgG4RD with lupus and the second interesting case had IgG4RD overlapping with 2 autoimmune diseases (lupus and rheumatoid arthritis) in the same patient. Both patients were treated with high-dose steroids and mycophenolate mofetil with good response, however, the second patient needed to be additionally treated with rituximab for better control of arthritis. Although uncommon, here, we report the first case series of 2 patients with IgG4 disease overlapping with other systemic autoimmune diseases. In our case series, the presence of the overlap did not impact the immediate clinical outcome or treatment response of IgG4RD or the co-existent systemic autoimmune disease.